2019
DOI: 10.1016/j.afjem.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Cola therapy for oesophageal food bolus impactions a case series

Abstract: Introduction This retrospective case series describes the use of cola to immediately treat complete oesophageal food bolus obstructions in the emergency centre. Short of emergent endoscopy – which is invasive, expensive, not without adverse events, and often unavailable in low-resource settings – no other proven therapies exist to relieve oesophageal food impactions. Methods We performed a chart review of adults with complete oesophageal food bolus obstructions presenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
(26 reference statements)
0
8
0
2
Order By: Relevance
“…They are commonly used, especially in resource poor countries, but the evidence supporting their use is limited to case reports and case series. 10 While a small 2019 South African series documented resolution of complete oesophageal obstruction in 13/22 (59%) cases with no adverse events, 11 other studies have reported complications including aspiration and oesophageal tear. 10 , 12 , 13 A 2005 review article reported success rate of 80% but a complication rate of 3% which exceeds that for therapeutic endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…They are commonly used, especially in resource poor countries, but the evidence supporting their use is limited to case reports and case series. 10 While a small 2019 South African series documented resolution of complete oesophageal obstruction in 13/22 (59%) cases with no adverse events, 11 other studies have reported complications including aspiration and oesophageal tear. 10 , 12 , 13 A 2005 review article reported success rate of 80% but a complication rate of 3% which exceeds that for therapeutic endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…On peut tenter de soulager l’obstruction œsophagienne aiguë par le bol alimentaire au moyen de modalités non effractives. La prise de boissons gazéifiées peut aider à déloger l’impaction alimentaire 48 . Si cette mesure se révèle inefficace, la personne devrait subir une endoscopie d’urgence.…”
Section: Prise En Charge De L’œsophagite à éOsinophilesunclassified
“…Si cette mesure se révèle inefficace, la personne devrait subir une endoscopie d’urgence. Le glucagon, la butylscopolamine, les anticalciques, les nitrates et les benzodiazépines se sont révélés inefficaces lors de plusieurs études 48 , 49 . Une radiographie du thorax avant l’endoscopie a toujours été recommandée pour exclure une perforation de l’œsophage, mais les lignes directrices actuelles ne la recommandent pas en raison du taux élevé de résultats faussement négatifs 49 .…”
Section: Prise En Charge De L’œsophagite à éOsinophilesunclassified
“…Historically, patients with food bolus obstruction were given intramuscular hyoscine butylbromide to relax oesophageal smooth muscle; and disimpaction rates of 100%,4 80%,5 and 57%6 have been reported in small cohort and case studies when fizzy drinks were given. However, systematic reviews78 found no evidence to recommend that any medical intervention is more effective than “watching and waiting.”78…”
Section: Answersmentioning
confidence: 99%